Deconstructing Deem and Pass: A Constitutional Analysis of the Enactment of Bills by Implication - Ronald J. Krotoszynski Jr. (Washington University Law Review, 2013)
Since 1933, the U.S. House of Representatives has maintained a procedure, the self-executing rule, that permits a single floor vote to pass multiple independent bills. Using this procedure, the House can pass a bill and, at the same time, “deem passed” entirely separate bills via a single floor vote. Some legal scholars have argued that this procedure is constitutionally unobjectionable, provided that members of the House clearly understand the legislative effects, whether singular or plural, of a particular vote. Others, however, have argued that the device violates the Constitution because the House and Senate do not vote on the same question. Careful consideration of the relevant constitutional text and legislative history reveals that the question does not have an easy or obvious answer. Perhaps surprisingly, the Constitution does not speak with clarity on whether a single floor vote may pass multiple, separate bills, nor does the Constitution’s legislative history provide any clear guidance on this question. Instead, the answer depends on whether one generally embraces formalism or functionalism in one’s separation of powers analysis. From a formalist perspective, the House and Senate must not only adopt the same identical text, but must also vote on the same question. From a functionalist perspective, however, the precise procedure used to approve the text should not matter so long as both the House and Senate take political responsibility for adopting a particular statutory text. Given the relatively weak reasons that undergird the House’s use of the deem-and-pass procedure—namely a desire to avoid political responsibility for unpopular legislation by rendering electoral accountability more difficult—the formalist position has much to recommend it.
Keywords: House of Representatives; deemed pass; formalism; legislation